The Role of Artificial Intelligence in The Optimization of Supply Chain Management - Loso Judijanto; Olyvia Rosalia (PT. Anagata Sembagi Education, 2025)
This research investigates the role of Artificial Intelligence (AI) in optimizing supply chain management. The study explores how AI technologies, such as predictive analytics, machine learning, and automation, contribute to enhancing efficiency, reducing operational costs, and improving decision-making accuracy in the supply chain. Data collected through interviews with industry practitioners and case studies from various companies reveal that AI significantly impacts demand forecasting, inventory management, and distribution planning. However, challenges such as limited infrastructure, a lack of skilled personnel, and integration issues with existing systems pose significant barriers to effective AI adoption. The findings highlight the importance of organizational readiness, technological infrastructure, and employee training in ensuring successful AI implementation. Ultimately, AI is shown to be a powerful tool in reducing uncertainty and increasing responsiveness within supply chains. This study provides valuable insights for businesses aiming to leverage AI for improving operational efficiency and competitiveness in the global supply chain landscape.